Ujęcie jakości życia w badaniu stanu zielonej gospodarki - Wyszkowska, Dorota; Artemiuk, Helena; Godlewska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Nature is a source of everything that surrounds us. Resources of our planet are, however, limited and the rate at which they are used leads to negative consequences not only for the globe, but also for its inhabitants. Pressure on environment is so great that it threatens the supply of resources to satisfy the residents’ needs and their wellbeing. Only responsible activity of humans in terms of development perspectives may limit excessive exploitation of natural environment and preserve it for future generations, while simultaneously lead to economic growth and development. One of such perspectives is the introduction of „green economy”. It is a set of activities undertaken to increase economic growth while taking due care of environment. “Green economy” involves monitoring of the efficiency of the aforementioned activities and of the state of greening the economy. Polish public statistics has put forth a set of measurements which can be used for this monitoring.The aim of this article is to evaluate the quality of life in Poland with the use of specially selected set of indices used to assess the state of green economy. This work consists of two parts.The first presents both theoretical aspects of green economy and indices to measure it. The other,however, focuses on Poland against the background of a selected group of indices, which can describe and assess the quality of life of Polish residents
Keywords: zielona gospodarka; jakość życia; monitorowanie wskaźników